Differential modulation of retinal degeneration by Ccl2 and Cx3cr1 chemokine signalling. - Luhmann, U; Lange, C; Robbie, S; Munro, P; Cowing, J; Armer, H; Luong, V; Carvalho, L; Maclaren, R; Fitzke, F; Bainbridge, J; Ali, R (2012)
Microglia and macrophages are recruited to sites of retinal degeneration where local cytokines and chemokines determine protective or neurotoxic microglia responses. Defining the role of Ccl2-Ccr2 and Cx3cl1-Cx3cr1 signalling for retinal pathology is of particular interest because of its potential role in age-related macular degeneration (AMD). Ccl2, Ccr2, and Cx3cr1 signalling defects impair macrophage trafficking, but have, in several conflicting studies, been reported to show different degrees of age-related retinal degeneration. Ccl2/Cx3cr1 double knockout (CCDKO) mice show an early onset retinal degeneration and have been suggested as a model for AMD. In order to understand phenotypic discrepancies in different chemokine knockout lines and to study how defects in Ccl2 and/or Cx3cr1 signalling contribute to the described early onset retinal degeneration, we defined primary and secondary pathological events in CCDKO mice. To control for genetic background variability, we compared the original phenotype with that of single Ccl2, Cx3cr1 and Ccl2/Cx3cr1 double knockout mice obtained from backcrosses of CCDKO with C57Bl/6 mice. We found that the primary pathological event in CCDKO mice develops in the inferior outer nuclear layer independently of light around postnatal day P14. RPE and vascular lesions develop secondarily with increasing penetrance with age and are clinically similar to retinal telangiectasia not to choroidal neovascularisation. Furthermore, we provide evidence that a third autosomal recessive gene causes the degeneration in CCDKO mice and in all affected re-derived lines and subsequently demonstrated co-segregation of the naturally occurring RD8 mutation in the Crb1 gene. By comparing CCDKO mice with re-derived CCl2(-/-)/Crb1(Rd8/RD8), Cx3cr1(-/-)/Crb1(Rd8/RD8) and CCl2(-/-)/Cx3cr1(-/-)/Crb1(Rd8/RD8) mice, we observed a differential modulation of the retinal phenotype by genetic background and both chemokine signalling pathways. These findings indicate that CCDKO mice are not a model of AMD, but a model for an inherited retinal degeneration that is differentially modulated by Ccl2-Ccr2 and Cx3cl1-Cx3cr1 chemokine signalling.